A DEWATERING SYSTEM STUDY WITH A NUMERICAL SOLUTION - Najla F. Al-Baejah; Aisha l Alzayani (Bani Waleed University Journal of Humanities and Applied Sciences, 2024)
Groundwater level management and control is a multidisciplinary process that calls for the collaboration of several experts in geotechnical engineering, hydrogeology, hydrology, geochemistry, hydrochemistry, etc. It is quite likely that some form of groundwater management is necessary for any new civil engineering project that involves building at altitudes below the water table. During excavation, a number of tried-and-true methods have been devised to decrease the groundwater table. The most often used techniques for dewatering include wells, sumps, and well points. Controlling the surface and subsurface hydrologic environment to enable "in the dry" building of the structure is the aim of construction dewatering. The majority of the analytical techniques for groundwater flow described in this handbook are for "steady-state" flow, not "unsteady-state" flow, which happens during the first stages of dewatering. By hydrostatic pressure and seepage, uncontrolled or incorrectly managed groundwater can induce heave, leakage, or decrease the stability of excavation slopes or foundation soils to the point that they are unfit for sustaining the structure. The methods used to address the resulting issues rely on a number of variables, including the size of the excavation, the type of soil, and the needs for groundwater control. Even the most basic dewatering procedures are performed without any thought beforehand. Advanced engineering and construction techniques are necessary for large-scale operations in challenging environments. The following categories best describe the primary goals of this paper: a) Analyze groundwater flow via porous media using numerical techniques (finite difference method); b) Present the theoretical findings of simulations of groundwater flow in the suggested research aquifer. c) Calculate the discharge, the number of well locations, and the distance between each well.